High-latitude stratospheric aerosols measured by the SAM II satellite system in 1978 and 1979 - Mccormick, M. P.; Chu, W. P.; Mcmaster, L. R.; Grams, G. W.; Hamill, P.; Steele, H. M.; Swissler, T. J.; Herman, B. M.; Pepin, T. J.; Russell, P. B. (1981)
Results of the first year of data collection by the SAM (Stratospheric Aerosol Measurement) II satellite system are presented. Almost 10,000 profiles of stratospheric aerosol extinction in the Arctic and Antarctic regions are used to construct plots of weekly averaged aerosol extinction versus altitude and time and stratospheric optical depth versus time. Corresponding temperature fields are presented. These data show striking similarities in the aerosol behavior for corresponding seasons. Wintertime polar stratospheric clouds that are strongly correlated with temperature are documented. They are much more prevalent in the Antarctic stratosphere during the cold austral winter and increase the stratospheric optical depths by as much as an order of magnitude for a period of about 2 months. These clouds might represent a sink for stratospheric water vapor and must be considered in the radiative budget for this region and time.